Empowering Rural Communities through Solar-Powered Irrigation Using a DC Pump for Sustainable Agriculture - Muhammad Hasim; Akmal Hidayat; Hamidah Hamris; Ummul Mansir; Aminuddin Aminuddin; Mudarris Mudarris; Iris Sumariyanto (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
Tondongkura Village has considerable potential for peanut farming but faces irrigation constraints due to hilly topography and dependence on gasoline-powered pumps. This community engagement program aimed to empower peanut farmers through a solar-powered irrigation system based on a DC pump as an appropriate technology for sustainable agriculture. A participatory approach was implemented through five stages: problem identification, system design, technology implementation, training and technology transfer, and mentoring and monitoring. The program involved 21 peanut farmers from the Bujung-Bujung Farmers Group. The results showed an increase in the average evaluation score from 36.3% to 72.1%, representing an improvement of 35.7 percentage points. The implementation strengthened farmers’ knowledge, skills, and independence in operating and maintaining the irrigation system while reducing dependence on fossil-fuel-based pumping. The program demonstrates the potential of solar-powered irrigation as an appropriate technology to support more efficient, energy-independent, and sustainable peanut farming.